A review of artificial intelligence studies in sports sciences - Gözen, I. (Turkish Journal of Sport and Exercise, 2025)
This article examines the bibliometric analyses of artificial intelligence studies in sports sciences using the Web of Science (WoS) database. Initially, 164 research articles were accessed from the WoS database, and the VOSviewer software package was used for data analysis. It was observed that the first publication related to artificial intelligence in sports sciences was published in 1995, with a significant increase in 2019, and the number of publications has shown an upward trend from 2023 to the present. The low number of publications in 2024 is due to only considering studies published up to July 2024. The most cited article, with 107 citations, is "Motor Unit Control and Force Fluctuation During Fatigue," while the author with the most publications, with six papers, is "Kunze, Kyle N." The most cited authors are "De Luca and Carlo J." with 171 citations. The journal with the most citations, (226), is "Knee Surgery, Sports Traumatology, Arthroscopy," and the institution with the most publications (8), is "Hosp Special Surg," while the institution with the most citations, (171), is "Boston Univ." The country with the most publications (23) and citations (613), is the USA. In the institutional collaboration network, among 11 institutions the highest collaboration was observed between the 8 institutions marked in red, while 3 institutions marked in green had fewer collaborations. In the co-keyword network, 12 keywords were identified, with the most dense clusters being red (machine learning) and yellow (artificial intelligence). In the authors` co-citation network,12 authors were identified, with the most cited cluster containing 7 authors in red, while the green clusters, consisting of 5 authors, had fewer citations. In conclusion, there has been a significant increase in publications related to the use of artificial intelligence in sports sciences in recent years, indicating a growing interest in the subject.